Multidirectional pharmacological effects of saponins in light of clinical trials: a systematic review of literature - Galas, Adam; Niemiec, Rafał; Matysek, Mikołaj; Olszanicka, Anna; Kołodziejczyk, Kacper; Hop, Izabela; Branewska, Justyna; Ostrowska, Barbara; Imioło, Jan; Maciąg, Anna (Journal of Education, Health and Sport, 2023)
Introduction: Saponins are secondary metabolites widely distributed in higher plants with multidirectional pharmacological effects. We distinguish between steroidal and triterpenoidal saponins, which are composed of glycone and aglycone. The varied medicinal properties of saponins are influenced by the presence of different substituents in the polycyclic aglycone, e.g. hydroxyls, hydroxymethyls, carboxyls and acyl groups, as well as the difference in bonding, composition and number of sugar chains. It is noteworthy that foods rich in these compounds can reduce the risk of developing various diseases, and the isolation of these compounds from the plant matrix provides new opportunities to create potential and effective drugs. Purpose of the work: Conduct a literature review on the basis of available clinical studies on the pharmacological effects of saponins extracted from medicinal plants and their potential application in medicine. Materials and methods: The work was based on a literature review of available medical publications from clinical trials conducted for the multidirectional therapeutic effects of saponins. Reports available in publications and scientific studies posted in medical information databases such as Pubmed and Google Scholar were summarised. Results: Clinical studies confirm the pharmacological effect of saponins in the treatment of sports injuries and trauma, type II diabetes, abnormal glycemic state fasting glucose, ischemic heart disease, pancytopenia and aplastic anemia. Conclusions: With the advancement of scientific research on saponins, it is possible to use them to produce potential drugs and dietary supplements with pharmacological effects. However, before saponins can be used for medical treatment, further research on their efficacy and safety is needed.